What do we know about the future of agriculture in Argentina, Brazil, Paraguay, and Uruguay? The Mercosur Outlook - Jorge, Nicolás; Campos, Silvia Kanadani; Gianatiempo, Juan Pablo; da Pereira, Vanessa da Fonseca; Masaro, Jimena Vicentin; Peri, Graciela Isabel; Piñeiro, Valeria (International Food Policy Research Institute, 2025)
This report constitutes a long-term vision for key variables of the agricultural sector in the Mercosur countries: Argentina, Brazil, Paraguay and Uruguay (or ABPU, with both terms used interchangeably). The objective is not to forecast the sector’s future but to serve as a reference tool, considering long-term drivers.